Child and adolescent psychotherapy : making the conscious unconscious. - Blake, Peter, 1950- ([S.l.] : Routledge, 2021)
In this new edition Blake gives a personal account of his professional experience of working with children and adolescents over the last 45 years. Providing a wonderful integration of the conceptual and the practical, this book clarifies complex theory while giving practical advice for clinicians through a nuts and bolts description of how to interview parents, emotionally assess a child and adolescent, set up a consulting room and conduct a therapy session. The addition of chapter summaries, questions and suggested further readings provides a valuable structure to those in child and adolescent training programmes. The author's experience, gained from public and private work, is vividly described with the use of clinical examples to illustrate his thinking and way of working. This third edition highlights his evolution from a more traditional epistemological (knowing) approach, with its emphasis on interpretation and insight, to a more ontological (being) framework. He explores a more intuitive and unconscious way of working and argues this is more developmentally appropriate to children and adolescents. His accessible writing style transports the reader into his clinical world: a world full of fascinating stories of children talking through their play; of adolescents exploring who they are through their discussions about music, films, sport and computer games; of helping parents to understand and thoughtfully manage their child's emotional struggles. This new edition, an amalgam of theoretical orientations (Kleinian, Bionian, Winnicottian, relational, non-linear and neurological), draws from recent developments, both in theory and technique. It will be of immense value to psychotherapists, psychoanalysts and all those involved in the treatment of children's mental health.
OCLC-licensed vendor bibliographic record.
Keywords: Child psychotherapy; Adolescent psychotherapy; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychotherapy / General